Avaliação de efeitos adversos da estimulação elétrica nervosa transcutânea (TENS) em ratas gestantes e na sua prole - Guimarães, Elisama de Campos (2019)
During pregnancy, some physiological and hormonal modifications facilitate the appearance of musculoskeletal disorders, especially low back pain, Although painful symptoms are common during pregnancy, prescription of drugs should be done with caution. In this context, the use of non-pharmacological resources has been an important tool, such as transcutaneous electrical nerve stimulation (TENS). However, studies on the application of TENS in the gestational period are scarce. Thus, The present study aimed to investigate the possible adverse effects of TENS in pregnant rats and their offspring. For this, a total of 30 female rats were divided into 6 groups (n = 5, per group): sensory TENS applied to the abdomen; motor TENS applied to the abdomen; sensory TENS applied in the paravertebral region; motor TENS applied in the paravertebral region; control with containment (CCC); control without containment (CSC). The estrous cycle of the rats was accompanied for programmed mating and the TENS applied on 10 consecutive days during the second gestational phase (11th to the 21st day of gestation) in the abdomen or paravertebral region of the pregnant rat, which was contained for current application. Of the offspring, from the programmed mating, a maximum of 3 males and 3 females were separated per pregnant rat. Of these, 9 males and 8 females were randomly selected per group ("n" delimited by the group that obtained the least number of pups), in order to perform the following tests: body mass and behavioral tests of mechanical sensitivity (von Frey filaments), thermal sensitivity (hot plate) and motor performance (activity monitor). Other parameters such as weight of rats during gestation, days for parturition and number of pups were also evaluated. The results showed that the pregnant rats of the TSA and TMA groups presented lower body mass in relation to the CCC. The TMP (male and female), TSP (male) and TMA (male) groups of offspring had a lower body mass from 60 days of birth compared to CCC. In addition, the TSP (male) and TSA (female) groups had a higher baseline mechanical threshold in the first month of life in relation to the CCC group. However, these findings were punctual and did not follow a pattern that could guarantee the action of TENS on these changes. The results related to the number of pups, days for parturition, thermal sensitivity and motor performance did not show differences between TENS and CCC groups. In this context, it is concluded that TENS did not promote changes in gestational and behavioral parameters that justify its contraindication during the gestational period.